HUMANISTIC HIERARCHY OF NEEDS ON AUGGIE'S PERSONALITY IN WONDER MOVIE - Rachmat Saleh Afif; Dina Amelia (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2021)
A humanistic theoretical perspective is a perspective that promotes conscious experience, personal responsibility, and the explanation of experience. Therefore, this research aims to describe the personality of Auggie in Wonder movie based on Humanistic Hierarchy of Needs’ theory.This research used descriptive qualitative method typically library research with textual analysis since data of this research are in the form of sentences and dialogues. The primary data source is Wonder movie (2017). This research used psychology of literature as the approach and used Maslow's theory of humanistic hierarchy of human needs (1987).The result of this research shows that Auggie’s personalities are clearly described through five classification based on the stage of humanistic hierarchy of needs and each explains the personality formed through Auggie’s process of fulfillment of his needs which are Wise, inferior, friendly and kind, smart, strong and brave.